Miejsce jazzu w polskiej edukacji muzycznej w latach 1960-1990. Postawy, deklaracje, fakty = The place of jazz in Polish music education in 1960-1990. Attitudes, declarations, facts - Niźnik, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article outlines the place of jazz in Polish musical culture, highlighting that it is chiefly shaped by the unfavorable stance of the precursors of Polish post-war musicology toward this genre. The materials presented in the text reveal a prevailing negative disposition among the Polish musicological community towards jazz, or even a lack of competence for its appropriate analysis. Such an outlook appears to adversely impact not only the status of music education in Poland but also the general level of artistic and aesthetic sensibility in contemporary Polish society.
Keywords: jazz; education; reception; musicology; PRL